2008
DOI: 10.1175/2007jamc1857.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Numerical Forecasts for Improving TMI Rain Retrievals over the Mountainous Area in Korea

Abstract: Topographical influences on the Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) rain retrievals over the terrain area of the Korean peninsula were examined using a training dataset constructed from numerical mesoscale model simulations in conjunction with radiative transfer calculations. By relating numerical model outputs to rain retrievals from simulated brightness temperatures, a positive relationship between topographically forced vertical motion and rain retrievals in the upstream region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Vicente et al (2002) developed a topographic correction technique for an IR-based rain retrieval such as the Hydro-Estimator (Scofield and Kuligowski 2003). Kwon et al (2008) recently developed topographic correction factors for terrain of the Korean Peninsula in the Goddard profiling (GPROF) algorithm (Kummerow et al 2001;McCollum and Ferraro 2003;Olson et al 2006;Wang et al 2009), which is the TRMM Microwave Imager (TMI) facility algorithm, as a function of terrain slope, low-level wind, and moisture parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vicente et al (2002) developed a topographic correction technique for an IR-based rain retrieval such as the Hydro-Estimator (Scofield and Kuligowski 2003). Kwon et al (2008) recently developed topographic correction factors for terrain of the Korean Peninsula in the Goddard profiling (GPROF) algorithm (Kummerow et al 2001;McCollum and Ferraro 2003;Olson et al 2006;Wang et al 2009), which is the TRMM Microwave Imager (TMI) facility algorithm, as a function of terrain slope, low-level wind, and moisture parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Following the study of Kwon et al (2008), we use parameters of terrain slope, low-level wind, and moisture. We introduce not topographical correction factors to the GSMaP algorithm, however, but rather the dynamic selection of lookup tables (LUTs) that are appropriate for orographic heavy rainfall, and we estimate rainfall rates from observed Tb using the LUTs.…”
Section: Introductionmentioning
confidence: 99%
“…Following the study by Vicente et al (2002) on the improvement of IR-based rain retrieval, Kwon et al (2008) developed topographic correction factors, as a function of terrain slope, low-level wind, and moisture parameters for the terrain of the Korean Peninsula in the Goddard profiling (GPROF) algorithm (Kummerow et al 2001;McCollum and Ferraro 2003;Olson et al 2006;Wang et al 2009), which is the TRMM Microwave Imager (TMI) facility algorithm. Recently, Shige et al (2013, hereafter S13) improved the performance of rainfall estimates made by the Global Satellite Mapping of Precipitation (GSMaP) MWR algorithm (hereafter GSMaP_MWR; Aonashi et al 2009;Kubota et al 2007) from TMI data for the Kii Peninsula, which is a region of heavy precipitation in Japan for which satellite methods of estimating the maximum rainfall amounts have been shown to be poor (Negri and Adler 1993;Kubota et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…S13 defined threshold values for these parameters and then applied the orographic precipitation profiles to those pixels where the threshold conditions were met. Several studies have suggested that orographic influence on precipitation is described better by a smoothed topography (Pedgley 1970;Vicente et al 2002;Kwon et al 2008); thus, it would be better to adopt a smoothed topography in calculating w oro . Therefore, the optimal horizontal length scale for averaging the elevation data as h in Eq.…”
mentioning
confidence: 99%
“…Despite the inclusion of two extratropical cyclone simulations (for warm-and cold-frontal regions), the land portion of the database was reduced to a relatively small number of profiles that represent the average tropical stratiform and convective rain conditions. These results strongly suggest the need to construct a regionally based GPROF database that can better explain a local rainfall system, as discussed in Kwon et al (2008) for cases of rain over South Korea. Wang et al (2009) compared TMI estimates with both the TRMM precipitation radar (PR) and rain gauge data used for the Global Precipitation Climatology Project (GPCP) and reported that the biases between TMI and both the PR and the GPCP gauge data were found to have strong seasonal variations.…”
Section: Introductionmentioning
confidence: 85%